PERSPEKTIF HUKUM ISLAM TENTANG ADAT DIAPPATONGKOI - A.sutra tenri awaru; Zulfahmi Alwi; A. Intan Cahyani (Universitas Islam Negeri Alauddin Makassar, 2022)
The principal problems of this writing is the perspective of Islamic law on indigenousdiappatongkoi soil (case study: district gantrang bulukumba) the principal problemsdivided into 3, namely: 1.how to customary practice diappatongkoi earth in kecamatan gantarang bulukumba. 2.how to view public figures related to thepresence of indigenous diappatongkoi land in kecamatan gantarang bulukumba.3.how the view of Islamic law on indigenous diapptongkoi land in kecmatangantarang bulukumba. this research is located in bulukumba kecamatan gantarang,south sulawesi province, the results of research in the find the author, among others.1 customary practice diappatongkoi land in kecamatan gantarang in bulukumba stillrife because of the many factors trigger that led to the practice of elopementdikecamatan gantarang bulukumba rife,2.the views of community leaders againstindigenous diappatongkoi land is inhumane because it has violated the rights of aperson and cause a person to lose the right 3.the view of Islamic law on indigenousdiappatongkoi tnaah in kecamatan gantarang bulukumba iala is not right because itshould be what becomes of the provisions had been set forth in the law of Islam.Based on what has been described above regarding the perspective of Islamic law onindigenous diappatongkoi soil (case study: district gantrang bulukumba), theresearchers want to give you the suggestions as follows : 1.For that parents need tosupervise the association of her children in order not to fall into free sex or juveniledelinquency, 2.Perhaps the figures of the Community is able to provide direction andpenejlasan related to how Islamic law is very influential in our Country, especially inIndonesia, a Country that is synonymous with law and rules.